Alcohol policy, multi-level governance and corporate political strategy: The campaign for Scotland's minimum unit pricing in Edinburgh, London and Brussels. (August 2021) - Hawkins, Benjamin; McCambridge, Jim
The Scottish government's plans for a minimum unit price for alcohol were vehemently opposed by the alcohol industry leading to a 6-year delay in implementation after legislation was passed. This article seeks to explain the consequences of devolution and European Union membership for the development of minimum unit price in Scotland through the concepts of multi-level governance, veto points and venue shifting. Systems of multi-level governance create policy interdependencies between settings, an increased number of veto points at which policies can be blocked, and the potential for policy actors to shift decision-making to forums where favourable outcomes are more likely to be attained. In the minimum unit price debates, the alcohol industry engaged in multiple forms of venue shifting and used regulatory compliance procedures and legal challenges at the EU level to try to prevent and delay the policy. This has led to a 'chilling effect' on subsequent alcohol policy developments across the United Kingdom.